(untitled) (International Journal of Engineering and Computer Science, 2017)
The people in old age or disabled people will have to stay at home, though their health exacerbates every day. The global population of people over the age of 65 is expected to more than double from 375 million in 1990 to 761 million in 2025. As the problem of aging and disability are converging, the smart home based health monitoring has become a key research area of ubiquitous and embedded computing system. The telehealth service has been widely implemented and used to help one (refers to elderly or individual with a disability) to live independently at home.The problems to be focused on, to improve the independence of old age people are their health, safety and reducing user assistance. These hurdles were the motivation factors for proposing the system. The main objective of this paper is to investigate techniques for using smart home technologies to monitor the day-to-day chores of old age people. The objectives are as follows: 1) identifying the problems faced by elderly people, 2) detecting difficulties in current data, and 3) designing a system which is senior citizen friendly. This paper is a solution that currently supports a set of functions that help home alone senior citizens to live independently. The idea of this project is to develop an intelligent and versatile home safety environment that could help the elderly and individual with disability live independently in their own home. The primary features of this project are Medicine Reminder and Scheduler, Programmable Remote, Health monitor, An enhanced fall detection system. This system offers the best features for improving the independent life of older population which includes providing a cost effective system for personal care and minimizing the financial burden upon the healthcare system.